hsa-miR-34a-5p Ameliorates Hepatic Ischemia/Reperfusion Injury Via Targeting HNF4α - Zheng, Xiaoqiang; Wang, Gang; Yuan, Jiang; Li, Nuoya; Yan, Biaolei; Yan, Jinlong; Sheng, Yanling (Turkish Journal of Gastroenterology, 2022)
Background: To investigate the relationship between the expression level of hsa-miR-34a-5p and liver injury and to further explore its regulatory signaling pathways Methods: Liver tissue and blood were collected from 60 patients undergoing hepatectomy. We constructed a rat HIRI model and treated it with an intraperitoneal injection of agomir-miR-34a-5p or agomir-normal control (NC) for 7 days after the surgery. The pathological changes of agomir-miR-34a-5p or agomir-normal control (NC) groups were compared. 7702 and AML12 cells were transfected with mimics NC or miR-34a-5p mimics and then treated with H2O2 for 6 hours. Cell apoptosis was detected by flow cytometry, Western blot, and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling, respectively. Furthermore, the target genes of miR- 34a-5p were identified by luciferase reporter gene assay and were verified in vitro. Results: The relatively high miR-34a-5p expression group revealed a lower level of alanine aminotransferase and aspartate aminotrans- ferase compared with the relatively low miR-34a-5p expression group. HIRI+agomir-miR-34a-5p rats exhibited significantly higher miR-34a-5p expression, lower serum alanine aminotransferase, aspartate aminotransferase, alleviated hepatic necrosis, reduced hepa- tocyte apoptosis, and decreased expression of apoptosis-related proteins, when compared with HIRI+agomir-NC rats (P < .05). After hydrogen peroxide treatment, alpha mouse liver-12 cell (AML-12) and normal liver cell line LO2 (LO2) cells transfected with miR-34a-5p mimics had significantly lower apoptosis rate compared with miR-34a-5p mimics NC group (P < .05). Hepatocyte nuclear factor 4α was identified as a miR-34a-5p target gene. Hepatocyte nuclear factor 4α expression was significantly downregulated in AML12 and HL-7702 (7702) cells transfected with miR-34a-5p (P < .05). Moreover, AML12 and 7702 cells transfected with miR-34a-5p signifi- cantly showed higher c-Jun N-terminal kinase (JNK), P38, cleavage cas-3, and BCL2 associated X (Bax) protein levels compared with AML12 and 7702 cells transfected with agomir-NC. Conclusion: miR-34a-5p possibly protected the liver from I/R injury through downregulating Hepatocyte nuclear factor 4α to inhibit the JNK/P38 signaling pathway. Cite this article as: Zheng X, Wang G, Yuan J, et al. hsa-miR-34a-5p ameliorates hepatic ischemia/reperfusion injury via targeting HNF4α. Turk J Gastroenterol. 2022;33(7):596-605.